Phytochemical Test of Sacha Inchi Oil from Central Java - Hadi, Mulyono; Permadi, Adi; Suharto, Totok Eka; Putri, Mutiara Wilson; Gulo, Herbert Alessandro Panias; Maema, Nadin Okta; Halimathusyakhdyah, Halimathusyakhdyah; Lupi, Ahmad (Universitas Ahmad Dahlan, 2025)
Sacha inchi oil is a seed-derived oil from the Amazon Rainforest, known for its high nutritional value and bioactive compounds. It contains essential fatty acids such as omega-3 and omega-6, along with tocopherols, polyphenols, carotenoids, and phytosterols, making it beneficial for health applications. Due to its nutritional and therapeutic properties, sacha inchi oil has gained significant attention in the food, cosmetic, and pharmaceutical industries. This study contributed to identify and analyze the bioactive compounds in sacha inchi oil extracted from seeds obtained in Central Java, Indonesia. The extraction process was carried out using a hot pressing method, followed by qualitative phytochemical analysis and LC-HRMS identification. The phytochemical tests confirmed the presence of flavonoids, alkaloids, tannins, phenolics, saponins, steroids, and terpenoids, all of which contribute to antioxidant, anti-inflammatory, anticancer, and antimicrobial properties. However, LC-HRMS analysis did not detect flavonoids, tannins, and saponins, possibly due to their low concentration, matrix effects, or degradation during analysis. These findings highlight sacha inchi oil’s potential in nutraceutical, pharmaceutical, and cosmetic industries. Its bioactive compounds suggest its potential use in functional foods, dietary supplements, and therapeutic applications, particularly in preventing oxidative stress-related diseases. Further research is recommended to optimize extraction techniques, improve compound stability, and evaluate its bioavailability and long-term health benefits. The presence of bioactive compounds indicates that sacha inchi oil can be a valuable functional ingredient for health and medical applications, contributing to sustainable and natural health solutions.